Highly Selective Conversion of HMF to 1‐hydroxy‐ 2, 5‐hexanedione on Pd/MIL‐101(Cr). Issue 37 (25th October 2019) - Yang, Yanliang; Xie, Yanfu; Deng, Dongsheng; Li, Dongmi; Zheng, Min; Duan, Ying
Abstract: Saturated cyclohexene water was used as the reductant for the preparation of Pd/MIL‐101(Cr). The catalysts were characterized by XRD, N2 adsorption/desorption isotherms, XPS, TEM, FTIR, ICP‐AES and in‐situ FTIR spectra of adsorbed pyridine. The water saturated by cyclohexene was proved to be an effective reductant to produce metallic Pd catalyst. The texture of MIL‐101(Cr) was kept well after the introduction of Pd to MIL‐101(Cr). The hydrogenation of HMF to 1‐hydroxy‐2, 5‐hexanedione (HHD) was conducted in water using Pd/MIL‐101(Cr) as catalyst. After reacted for 6 h at 413 K 4 MPa H2, up to 82% yield of HHD was achieved without acid additives. The MIL‐101(Cr) acted both as support and acid catalyst generated from the open Cr 3+ . The stability of the catalyst was investigated to find that the TOFs decreased slightly after the catalyst was used. The decline in the catalytic activity was discussed and ascribed to the condensation of intermediates on the active sites and the partly aggregate of Pd. Abstract : Pd/MIL‐101(Cr) was prepared employing saturated cyclohexene water as the reductant. The cyclohexene was proved to be an effective reductant for the reduction of PdCl2 at very mild conditions. 82% yield of 1‐hydroxy‐2, 5‐hexanedione was obtained by the hydrogenation of HMF on Pd/MIL‐101(Cr) catalyst without any acid additives. The used catalyst was characterized to find the reasons for the slight decrease in activity.